Strengthening Community Digital Literacy through Information Technology Utilization Training in Deli Serdang Regency - Muhammad Walimsyah Sitorus (EPISTEMOLOGI : JURNAL PENGABDIAN MASYARAKAT DAN PENELITIAN, 2025)
Digital transformation requires communities not only to be able to use technological devices, but also to search for and verify information, protect data, interact ethically, and use technology productively. This community service activity aimed to improve community digital literacy through training in the use of information technology in Deli Serdang Regency. The program was designed using a participatory approach and guided practice involving 40 participants. The activity stages consisted of needs identification, pretest, material delivery, demonstration, practice, mentoring, posttest, and evaluation. The materials were organized around four pillars of digital literacy: digital skills, digital safety, digital ethics, and digital culture. The evaluation instrument consisted of 20 items with a maximum score of 100. Simulated evaluation data showed a total pretest score of 2,290 with a mean of 57.25, while the total posttest score was 3,415 with a mean of 85.38. The mean increased by 28.13 points, with an N-gain of 0.67, which is in the moderate category. A paired-samples t-test showed a significant difference between scores before and after the training, t(39) = 20.51; p < 0.001. The largest improvements were observed in the ability to recognize phishing, use two-factor authentication, verify information sources, and protect account security. The program indicates that contextual, participatory, practice-based training has the potential to strengthen community digital competence. Program sustainability requires periodic mentoring and collaboration among higher education institutions